2020
DOI: 10.1007/s41809-020-00058-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and brain reserve in bilinguals: field overview and explanatory mechanisms

Abstract: There is an ongoing debate on potential neuroprotective effects of bilingualism against cognitive decline during healthy aging. In this paper, we consider the neural and cognitive mechanisms through which these protective effects may operate. We review the evidence suggesting that bilingualism can act as a booster of neuroplasticity and/or as a brain protection mechanism providing effective compensation. Our main aim is to better define the linkage between reserve and lifetime bilingual experience and their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 134 publications
0
12
0
Order By: Relevance
“…One might also speculate that the phenomenon reported here might constitute the source of the enhanced cognitive reserve observed in senior bilinguals (see Gallo et al, 2020). Our findings indicate that experienced bilinguals show optimal task performance in the face of GMV variations, with no effect of decreasing volumes on performance levels.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…One might also speculate that the phenomenon reported here might constitute the source of the enhanced cognitive reserve observed in senior bilinguals (see Gallo et al, 2020). Our findings indicate that experienced bilinguals show optimal task performance in the face of GMV variations, with no effect of decreasing volumes on performance levels.…”
Section: Discussionmentioning
confidence: 66%
“…The DRM explains the trajectory of bilingualism-induced neuroplasticity as pruning: bilinguals would develop extra connections to accommodate the increased language control effort, to subsequently eliminate the supernumerary connections once the more efficient ones are identified. This process would also account for the resilience to age-related neurodegeneration observed in aging bilinguals (see Gallo, Myachykov, Shtyrov & Abutalebi, 2020): the efficient connections surviving this pruning phase would also be the ones that survive age-related deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, CR is the individual ability to compensate for agerelated neural deterioration and maintain optimal cognitive functioning. Many lifestyle factors have been suggested to promote successful aging by means of CR development (for a review see Cheng, 2016), and bilingualism has been implicated as one such factor (for a review see Gallo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, existing research has reported the beneficial effects of bilingualism beyond the language system-by showing positive bilingual effects on the general cognitive abilities, including memory (Soliman 2014;Hernández et al 2012), attention (see Bialystok 2015, for review), and executive function (Abutalebi et al 2013;Antoniou et al 2016;Morales et al 2015)-to the general cognitive systems involved in parallel monitoring, inhibition, and control of linguistic processing in two or more languages. Importantly, this general effect is accompanied by neuroanatomical structural changes such that higher L2 proficiency levels are associated with more efficient functional connectivity in the brain areas supporting executive control (Sulpizio et al 2020;Gallo et al 2020Gallo et al , 2021. Although still controversial and presently a subject of fierce debate (see for instance Paap and Greenberg 2013), these facilitatory "bilingual effects" are an example of how an increase in L2 proficiency may affect both linguistic and general cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%